2020
DOI: 10.1186/s13756-020-00820-8
|View full text |Cite
|
Sign up to set email alerts
|

A nosocomial cluster of vancomycin resistant enterococci among COVID-19 patients in an intensive care unit

Abstract: Background Currently, hospitals have been forced to divert substantial resources to cope with the ongoing coronavirus disease 2019 (COVID-19) pandemic. It is unclear if this situation will affect long-standing infection prevention practices and impact on healthcare associated infections. Here, we report a nosocomial cluster of vancomycin-resistant enterococci (VRE) that occurred on a COVID-19 dedicated intensive care unit (ICU) despite intensified contact precautions during the current pandemic. Whole genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 25 publications
(22 reference statements)
2
61
1
4
Order By: Relevance
“…( 30 , 31 ) The spread of VRE to COVID-19 patients in a healthcare setting has been demonstrated through the application of WGS in work conducted at the University Hospital Münster in Germany. ( 32 ) The researchers detected clonally-related isolates of VRE in both ICU patients and in environmental samples indicating a role for contaminated surfaces in VRE transmission to COVID-19 patients. ( 32 ).…”
Section: Covid-19 and Antibiotic-resistant Healthcare-associated Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…( 30 , 31 ) The spread of VRE to COVID-19 patients in a healthcare setting has been demonstrated through the application of WGS in work conducted at the University Hospital Münster in Germany. ( 32 ) The researchers detected clonally-related isolates of VRE in both ICU patients and in environmental samples indicating a role for contaminated surfaces in VRE transmission to COVID-19 patients. ( 32 ).…”
Section: Covid-19 and Antibiotic-resistant Healthcare-associated Infectionsmentioning
confidence: 98%
“…( 32 ) The researchers detected clonally-related isolates of VRE in both ICU patients and in environmental samples indicating a role for contaminated surfaces in VRE transmission to COVID-19 patients. ( 32 ).…”
Section: Covid-19 and Antibiotic-resistant Healthcare-associated Infectionsmentioning
confidence: 99%
“…While experts have warned of the link between COVID-19 and AMR [ 3 - 8 ], studies report conflicting evidence. Several studies—from, in particular, Germany, Italy and the US—have reported outbreaks or an increase in infections with and/or acquisition of multidrug-resistant bacteria during the COVID-19 pandemic [ 9 - 12 ]. Further studies have reported cases of antimicrobial-resistant invasive fungal infections in COVID-19 patients [ 13 , 14 ], and one case of azole-resistant Aspergillus spp.…”
mentioning
confidence: 99%
“…Experts have already warned about the link of COVID-19 and antibiotic-resistant microbes [141] , [142] . Few countries have reported an increased number of cases related to multi-drug resistant microbes during the COVID-19 pandemic [141] , [143] , [144] , [145] , [146] . The execution of light-active TiO 2 coatings is an outstanding option to fight against the antibiotic-resistant strains developed in several environments such as shared touch surfaces, healthcare environments, water resources, agriculture, food, etc .…”
Section: Challenges and Prospectsmentioning
confidence: 99%